The Training of Color Gradation in Developing Teachers’ Competent of Early Childhood Education and Raudhatul Athfal (RA) Maarif at Metro City - Muhammad Yusuf; Masrurotul Mahmudah; Sindi Sintia (Yayasan Payungi Smart Madani, 2023)
Based on the initial observations made by the author that most teachers do not understand the concept of gradation and have not been able to apply color gradations in pictures. The article aims to give an assistance of Training of Color Gradation for Teachers’ Early Childhood Education and Raudhatul Athfal (RA) Maarif at Metro City to develop teachers’ competence. The method used ABCD (Asset Based Community) to maximize the potential assets, which includes individual assets, communities, infrastructure, community, et al. This activity is specifically for Early Childhood Education teachers and Raudhatul Athfal Teachers Maarif in Metro City for 2 days. The implementation stages include carrying out an initial test through the process of coloring pictures, after that training is carried out, then practice and evaluation of the coloring results. The result shows that the teachers understand coloring techniques using color combinations, teachers can be creative with more interesting and sharp images and colors, teachers' fine motor skills have increased, so they are more confident when receiving personal drawing and coloring services Keywords: Training of Color Gradation, Developing Teachers’ Competent, Color Gradation